2016
DOI: 10.14488/bjopm.2016.v13.n3.a14
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines to Risk Management Maturity in Construction Projects

Abstract: Purpose -This article aims to provide the guidelines to assess the risk management maturity (RMM) of construction projects.Design/methodology/approach -This article presents a literature review of the main risk management models, which aims to support a survey research to define, according to experts, the market preference and knowledge of RMM models.Findings -We pointed out in this article a set of guidelines to direct the maturity analysis of RM in the Construction Industry and proposed a model matrix to hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
1
6
0
2
Order By: Relevance
“…Presenting a specific and practical delineation of a risk management maturity framework, Dellana et al (2021) avers that industry-wide successful adoptions of the framework anchor on three phases of orientation, integration and collaboration. This three-phase fragmentation also finds empirical agreement in extant literature (Caiado et al, 2016;Oliva, 2016), and has semblances of the organizational learning concept of knowledge acquisition, integration and collaboration (Belinskia et al, 2020;Kordab et al, 2020;Sari & Sukmasari, 2018).…”
Section: Organizational Learning and Risk Management Maturity: System...supporting
confidence: 64%
See 1 more Smart Citation
“…Presenting a specific and practical delineation of a risk management maturity framework, Dellana et al (2021) avers that industry-wide successful adoptions of the framework anchor on three phases of orientation, integration and collaboration. This three-phase fragmentation also finds empirical agreement in extant literature (Caiado et al, 2016;Oliva, 2016), and has semblances of the organizational learning concept of knowledge acquisition, integration and collaboration (Belinskia et al, 2020;Kordab et al, 2020;Sari & Sukmasari, 2018).…”
Section: Organizational Learning and Risk Management Maturity: System...supporting
confidence: 64%
“…The results show a significant influence of information acquisition and shared interpretation on RMM. The study concluded that organizational learning was a key factor in organization maturity Caiado et al (2016). examined factors that aid the development of guidelines for assessing the risk management maturity (RMM) of construction projects.…”
mentioning
confidence: 99%
“…As mudanças provenientes de um ambiente de negócios, ou do mercado, ou das inovações tecnológicas ou ainda da regulação, devem ser consideradas em conjunto com as estratégias corporativas. Para isto, o alinhamento gerencial através de uma gestão top-down é fundamental, associado ao comprometimento e a pro-atividade dos líderes, bem como a um processo decisório transparente, participativo, com comunicação a todos os stakeholders e a responsabilização coletiva por riscos e oportunidades (Caiado et al 2016).…”
Section: Consequências Sobre O Direcionamento Estratégicounclassified
“…Measuring the maturity of the project risk management systems edifies the evaluation and elimination of the weaknesses that undermine the effectiveness of the local government project risk management. [1] Improved effectiveness of project risk management approach is critical for leveraging the effective performance of the contemporary public sector organisations. [2] This is attributable to the fact that the local government sphere relies on the conceptualisation and implementation of an array of different socio-economic projects as the means for responding to the different socio-economic needs and demands of the population.…”
Section: Introductionmentioning
confidence: 99%